1984
DOI: 10.1016/0021-9797(84)90218-2
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation from supersaturated aluminate solutions. II. Role of temperature

Abstract: The effect of temperature on the precipitation of aluminum hydroxide from dilute potassium aluminate solutions (C~a Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
3
8

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 17 publications
2
19
3
8
Order By: Relevance
“…E a values of 160 ± 20 and 158 ± 20 kJ mol −1 were calculated for nucleation from sodium and potassium aluminate solutions, respectively. These values are higher than the 95 ± 10 kJ mol −1 reported for the nucleation of pure bayerite (41), which exhibits faster crystallization kinetics than gibbsite. The present value is also higher than 55 kJ mol −1 reported for the growth of Al(OH) 3 bayerite and gibbsite (23,41).…”
Section: Order Of Reaction and Activation Energy Of Nucleationcontrasting
confidence: 49%
See 1 more Smart Citation
“…E a values of 160 ± 20 and 158 ± 20 kJ mol −1 were calculated for nucleation from sodium and potassium aluminate solutions, respectively. These values are higher than the 95 ± 10 kJ mol −1 reported for the nucleation of pure bayerite (41), which exhibits faster crystallization kinetics than gibbsite. The present value is also higher than 55 kJ mol −1 reported for the growth of Al(OH) 3 bayerite and gibbsite (23,41).…”
Section: Order Of Reaction and Activation Energy Of Nucleationcontrasting
confidence: 49%
“…The value obtained in the present work is comparable to 45 ± 6 mJ m −2 reported by (11), from gibbsite nucleation studies in which a rather low β value of 2.2 (<β = 16.8 for sphere) was used. γ of 67 ± 20 and 25 mJ m −2 have been respectively estimated for bayerite and pseudoboehmite crystallization (40,41), while 140 mJ m −2 was determined from apparent solubility of gibbsite in saturated aqueous solutions (25,42).…”
Section: Estimation Of the Interfacial Energymentioning
confidence: 99%
“…This would appear to be related to aluminium solubility at high pH. Earlier studies (24,25) showed that in supersaturated aluminium solutions, the sequence of aluminium hydroxide precipitation is "amorphous-pseudoboehmite-bayerite". In other words, rapid precipitation in alkaline aluminate solutions generates bayerite.…”
Section: Discussionmentioning
confidence: 97%
“…De nuevo este comportamiento parece estar relacionado con la solubilidad del aluminio a elevados pH. En trabajos previos (24,25) se ha demostrado que en disoluciones sobresaturadas de aluminio a temperatura ambiente la secuencia de precipitación del hidróxido de aluminio es "amorfo-pseudoboehmite-bayerita". Es decir, la precipitación rápida de las disoluciones de aluminatos alcalinos produce bayerita.…”
Section: Discussionunclassified
“…bajerit, nordstrandit, slabo kristalni bemit [1,2,4]. Kristalizacija dobro kristalnog bajerita uglavnom preovlađuje iz razrijeđenih rastvora aluminata (≤ 1M NaOH) [8], dok kod koncentrovanih rastvora (≥2,5 M NaOH) [7,8] preovlađuje gibsit. Rastvori srednjih koncentracija (1,0-2,5 M NaOH) daju smješu gibsita i bajerita.…”
Section: Uvodunclassified